1990
DOI: 10.3138/483m-2n11-t168-7436
|View full text |Cite
|
Sign up to set email alerts
|

Can young children use maps to navigate?

Abstract: There are opposing points of view as to what map tasks children can perform as well as understand. Some studies have indicated a low level of map skills ability in children up to 10 years old, whereas others indicate that children already possess a variety of map-use skills before the age of school entrance. This study examines the ability of preliterate children ages 4, 5, and 6 to use a map for navigation. An obstacle course was utilised which the child attempted to navigate on a predetermined path outlined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1
3

Year Published

1991
1991
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
0
10
1
3
Order By: Relevance
“…Studies of way nding and navigation abilities of pre-literate children have shown that by the age of 4, young children can kind their ways around familiar neighbourhoods and interpret some aspects of maps and aerial photographs (Hazen et al 1978, Spencer and Blades 1985, Freundschuh 1990, Blaut 1997, Blades et al 1998 ). However, we know of no literature on other aspects of geographical concepts that young children have mastered, especially the development of geospatial object concepts.…”
Section: T He Primary Theory Of the Geographical Domainmentioning
confidence: 96%
“…Studies of way nding and navigation abilities of pre-literate children have shown that by the age of 4, young children can kind their ways around familiar neighbourhoods and interpret some aspects of maps and aerial photographs (Hazen et al 1978, Spencer and Blades 1985, Freundschuh 1990, Blaut 1997, Blades et al 1998 ). However, we know of no literature on other aspects of geographical concepts that young children have mastered, especially the development of geospatial object concepts.…”
Section: T He Primary Theory Of the Geographical Domainmentioning
confidence: 96%
“…According to the findings of many researchers (Bartz, 1970;Freundschuh, 1990;1981, 1993Matthews, 1984aMatthews, , b, 1992Rushdoony, 1969;Stimpson, 1987;Spencer et al, 1989;Walker, 1980;Wilson, 1980) children demonstrate the ability to conceptualise information from maps at quite an early age. Some studies reveal the difficulties faced by young children from seven to 12 years in of conceptualising map-related knowledge, though there is also evidence that it develops and progresses with age (Dale, 1971;Liben & Downs, 1989;Satterly, 1964;Tierney, 1985).…”
Section: Introductionmentioning
confidence: 95%
“…Children from four to six years o f age are able t o comprehend aerial photographs (Blaut and Stea 1971;replicated by Spencer, Harrison, and Darvizeh 1980), recognize symbols on maps (Blades and Spencer 1987a), retain information about the angle and direction of mapped o bjects (Blades and Spencer 1989;Landau 1986), and understand the relations between world space and map space (Ottosson 1988). Con-trary to Piagetian doctrine, six-year old children are able to use simple maps to navigate obstacle courses (Freundschuh 1990). As Wood (1984) suggests, the cultural schema for map interpretation and use may b e learned prior to the start of formal schooling.…”
Section: General Map Knowledgementioning
confidence: 99%